Modeling and Analysis of Integrated Electric Energy Metering Information System Integrating Operational Behavior of Interactive Robots (Informatica, 2024)
A difficult problem to solve always exists in the accuracy of power quality monitoring. Even if various calculation methods such as Fourier and Bayes are used, the expected prediction effect hasn't been achieved. Today, with the advancement of information processing technology and signals, based on the advantages of the previous basic calculation methods, the interactive robot model is proposed again. It is a derivation based on machine learning calculation method, which can achieve good budget value without sacrificing the essence of calculation speed and accuracy in the application environment of overload. The intelligent exercise research based on the operation specification of the interactive robot mentioned in this paper can continuously strengthen the power numerical change model by detecting the electric power value, and apply it to the electric energy calculation information integrated system platform, so as to achieve the predicted result as the most ideal state. The experimental results of the imitation experiment prove the executable direction of the interactive robot operation specification, and provide theoretical data for the future upgrade and improvement of the electric energy metering system